Fragmentation, incomes and jobs: an analysis of European competitiveness - Marcel P. Timmer; Bart Los; Robert Stehrer; Gaaitzen de Vries (European Central Bank (ECB), 2013)
Increasing fragmentation of production across borders is changing the nature of international competition. As a result, conventional indicators of competitiveness based on gross exports become less informative and new measures are needed. In this paper we propose an ex-post accounting framework of the value added and workers that are directly and indirectly related to the production of final manufacturing goods, called "manufactures GVC income" and "manufactures GVC jobs". We outline these concepts and provide trends in European countries based on a recent multi-sector input-output model of the world economy. We find that since 1995 revealed comparative advantage of the EU 27 is shifting to activities related to the production of non-electrical machinery and transport equipment. The workers involved in manufactures GVCs are increasingly in services, rather than manufacturing industries. We also find a strong shift towards activities carried out by high-skilled workers, highlighting the uneven distributional effects of fragmentation. The results show that a GVC perspective is needed to better inform the policy debates on competitiveness.
Keywords: F6; J2; O47; O57; 330; European competitiveness; fragmentation; incomes and jobs; Export; Internationale Arbeitsteilung; Internationaler Wettbewerb; Beschäftigungseffekt; Input-Output-Analyse; Europa